TINGKAT KEPUASAAN KERJA KARYAWAN PADA PT PELINDO SAMARINDA - ., Nursali (PREDIKSI, 2012)
Data were analyzed using average figures so as to categorize respondents by 50 people out of a population of 150 people. Based on the average value of the six indicators or sub-indicators eighteen / item questionnaire to measure Employee Satisfaction variable of Employee Satisfaction obtained average variable Employee Job Satisfaction of 3.46, suggesting that level of employee satisfaction Pelindo Samarinda is Satisfactory, that hypothesis is accepted.